Desarrollo de una propuesta de un tratamiento biológico con hongos de la podredumbre blanca para la degradación de fenoles en efluentes de la empresa Laboratorios Esko LTDA (2021)
Phenol has a toxicity associated with its concentration and therefore the industrial effluents that contain it must be treated before being discharged into the environment. Due to the bactericidal properties of phenol, these effluents cannot be treated in conventional treatment plants, at concentrations greater than 50 mg/L it inhibits the reproduction of microorganisms and at concentrations of the order of 1 g/L they completely destroy the flora and fauna. Taking into account the above, in this research a proposal is made to complement the processes of the WWTP of the company Laboratorios ESKO Ltda, having as its main objective the degradation of phenolic compounds, to comply with current regulations (Resolution 0631 of 2015) for the disposal of reuse waters and discharges.